ANALISIS PERSEPSI MAHASISWA TERHADAP PENGEMBANGAN SOFT SKILLS DI PERGURUAN TINGGI - Siti Almaidah (Riset Manajemen dan Akuntansi, 2016)
The purpose of this study was to obtain an overview of the characteristics of students and analyze their perceptions of the development of soft skills, the study was conducted on students of private universities in Surakarta. Soft skills are needed so that students have the ability to relate well to others. At present the ratio of the need for soft skills and hard skills to the world of work is inversely proportional to its development in universities. Soft skills are only given an average of 10% in the curriculum. Meanwhile in the world of work, human resources are required to have adequate hard skills and are proficient in their soft skills. The population in this study were all students at Private Universities in Surakarta. While the sample is 60 students. The sampling technique was carried out by purposive sampling technique. Data analysis method was carried out by using univariate research instruments and analysis. Based on the results of the analysis it can be concluded that students have a positive perception of the development of attributes of soft skills in the form of communication skills, leadership, self-organization, and entrepreneurship. Keywords:Perception, Students, Private Universities, Soft Skills.